Manipulative Approach In Teaching Fractions - Parungao, Rea C. (Future Science / FSH-PH Publications, 2021)
This study aimed to determine the effects of using manipulatives in teaching fractions. Quasi- experimental method of research was used in this study. It was conducted during the first quarter of S.Y. 2019-2020 among the respondents were randomly selected. Two sections of Arayat National High School were the respondents of the study. The control group was the 7-Rosal while the 7-Sampaguita was the experimental group. Both groups were given a pretest prior to the discussion about fractions and a posttest after instruction using the traditional method (control group) and the use of manipulatives (experimental group). The results were then evaluated, analysed through SPSS, and interpreted. Mean, t-test and ANCOVA were utilized to analyze and interpret the data. This study found out that the post-test scores of the respondents from the two groups improved in comparison to their pre-test scores. The mean pretest and mean posttest scores of both groups showed significant difference. The results showed that the use of virtual manipulatives in converting fractions to decimals had significant difference compared the use of the traditional method. On the contrary, teaching fractions on a number line did not have significant difference. Out of the four operations on fractions, three showed that the use of concrete manipulatives was highly effective. This study recommends that teachers must test the prior knowledge of their students before discussing about fractions to determine the students’ strengths and weaknesses. Although both traditional method and the manipulative approach showed improvement on the post-test results in teaching fractions, still, teachers are encouraged to use manipulatives in teaching fractions to improve students’ performance. It is important for teachers to provide their students opportunities for hands-on manipulation of objects in order to grasp the concepts of fractions more easily. Lastly, teachers must develop the use of concrete and virtual manipulatives in teaching fractions to promote active learning that can enhance students’ mathematics performance and can help them to realize that mathematics is an enjoyable subject.